(untitled) (Journal of Nepal Geological Society, 2024)
This study examines arsenic contamination in groundwater wells in the Rajpur Municipality, Rautahat District, Nepal. Susceptibility of arsenic effects in the Terai region is the main reason to select Rautahat District for the study. Forty-five samples of groundwater wells were collected from nine wards (Pipra Bhagwanpur, Phatuha Maheshpur, Damarchuk, Rajpur Farhadwa, Kudiya, Akolwa, Baluwa, and Bairiya) in shallow wells (<50 m, 80%) and deep wells (>50 m, 20%). The depths of the wells ranged from 7.6 to 82.4 m. The arsenic in 28.9% of the groundwater wells were within World Health Organization (WHO), 2017, drinking water quality guideline value of 0.010 mg/L. The samples of 80.0% of groundwater wells were within Nepal drinking water quality standard (NDWQS), 2022, for arsenic of 0.050 mg/L. The arsenic, iron, and manganese concentrations were in the range of below the detection limit (BDL) to 0.220 mg/L, BDL to 6.30 mg/L, and 0.04 to 1.50 mg/L, respectively. Additionally, the mean concentrations of arsenic, iron, and manganese were recorded as 0.040 mg/L, 0.78 mg/L, and 0.39 mg/L, respectively. The low Oxidation Reduction potential (ORP) in most of the groundwater wells indicates that the mobilization of arsenic, iron, and manganese in the groundwater is favorable in reducing environment. A slight positive correlation between pH and arsenic implies that arsenic mobilization is favorable at high pH. Similarly, the slight negative correlation between arsenic and depth of the groundwater wells visualizes elevated levels of arsenic in the shallow groundwater wells. There are positive correlations between arsenic, iron, and manganese. In addition, principal component analysis (PCA) indicates common natural sources for these metals. Spatial distribution patterns reveal elevated levels of EC, iron, manganese, and arsenic in many wells, indicating high mineralization.